Use elimination method to solve
5x+y=-10
7x-3y=-36

Answers

Answer 1
Answer: 5x+y=-10\n \n 7x-3y=-36

Let's multiply the first equation by 3. (As you can see y's coefficient in the first one is 1 and in the second one is -3 , we will multiply the first equation by 3 so when we add the equations their sum will be 0)

3\cdot (5x+y)=3\cdot -10\n \n 15x+3y=-30

Now let's add this new equation and our second equation.

7x-3y=-36\n \n 15x+3y=-30\n \n (15x+3y)+(7x-3y)=(-30)+(-36)\n \n 15x+7x+3y-3y=-30-36\n \n 22x=-66\n \n x=\frac { -66 }{ 22 } \n \n x=-3

We found x=-3

Now let's plug x's value in one of the equations to find y's value.

x=-3\n \n 5x+y=-10\n \n 5\cdot -3+y=-10\n \n -15+y=-10\n \n y=-10+15\n \n y=5

So we found y=5

Solution ;

(-3, 5)


Related Questions

Pls help it’s 12 POINTS!!!
Which of the following is an infinite set?the set of lessons in this course the set of even numbers from 0 to 10 10 billion the set of integers the null set none of the above
The scale factor, k, is 2. How does the size of the image relate to the pre-image?
Write the quadratic equation in standard form. What is the value of b 2 - 4ac?1 = 2x 2 + 7x
Jordan can ride his bike 24 miles in 2 hours. How many miles can he ride his bike in 5 hours?​

A local store is advertising a shirt on sale for 40% off the original price. The sale price is $21.00. What was the original price for the shirt?

Answers

Answer:

  $35

Step-by-step explanation:

If $21 is 60% of the original price, then the original price is ...

  21 = 0.60p

  21/0.60 = p = 35

The original price is $35.00.

Answer:

$35

Step-by-step explanation:

If $21 is 60% of the original price, then the original price is ...

 21 = 0.60p

 21/0.60 = p = 35

The original price is $35.00. , hope it helps i answered last time but was deleted

On a coordinate grid, point A is at (−3.0, −5.4) and point B is at (−3.0, 5.4). Point B is a reflection of point A across the ___–axis. Input either a lowercase x or y.

Answers

Given:
Point A (-3.0,-5.4)
Point B (-3.0,5.4)

reflection across y-axis ⇒ (a,b) reflected (-a,b)
reflection across x-axis ⇒ (a,b) reflected (a,-b)
reflection across the origin ⇒ (a,b) reflected (-a,-b)
reflection on y = x ⇒ (a,b) reflected (b,a)

Point B is a reflection of Point A across the x-axis.

Answer:

X- axis

Step-by-step explanation:

suppose that the function f(x) = 4x - 2 represents the cost to rent x movies a month from an internet movie club. laticia now has $12. how many more dollars does laticia need to rend 5 movies next month?

Answers

5 movies
5 for x
f(5)=4(5)-2
f(5)=20-2
f(5)=18

she nees 18
she has 12
18-12=6
she needs $6 more

You are wanting to simulate tossing a coin 20 times to determine the probability of getting tails. Starting with the first row, you use the list of random numbers shown to do so, letting 0-4 represent heads and 5-9 represent tails. What is the probability the coin lands on tails?

Answers

When you flip a fair coin, there is always a 50% chance of heads, and a 50% chance of tails. Not sure the rest of info is relevant here

Final answer:

Simulated coin tossing uses random numbers, where 0-4 and 5-9 represent heads and tails respectively. The theoretical probability of getting tails is 0.5, but empirical probabilities can differ. This discrepancy, assumed to reduce with more trials, is accounted for by the Law of Large Numbers.

Explanation:

In the context of the provided problem, you are attempting to simulate tossing a coin 20 times using a system of random numbers, where you've assigned 0-4 to represent heads and 5-9 to represent tails. Theoretically, in a fair coin toss, there's a 50% chance (0.5 probability) of getting either heads or tails.

However, experimental or empirical probability may not always align with this theoretical likelihood, especially in smaller samples. This discrepancy is due to randomness and doesn't necessarily imply the coin or system is biased. Over many trials, the relative frequency of getting tails should approach the theoretical probability, according to the law of large numbers.

To calculate the empirical probability of getting tails in your simulation, you would tally up the total number of 'tails' results (numbers 5-9) from your 20 trials, then divide that count by the total number of trials (20). So, if you get 12 'tails' results, your empirical probability would be 12/20 = 0.6.

Learn more about probability here:

brainly.com/question/32117953

#SPJ3

A student earns $7.50 per hour at her part-time job. She wants to earn at least $200.Enter an inequality that represents all of the possible numbers of hours (h) the student could work to meet her goal.

Enter the least whole number of hours the student needs to work in order to earn at least $200

Answers

Answer: 7.50 h  ≥200

She needs to work  27 hours to earn at least $200.

Step-by-step explanation:

Hi, to write the inequality we have to analyze the information given:

  • Earnings per hour : $7.50
  • Hours : h
  • She wants to earn at least $200.

So, she earns $7.50 per hour, the expression that represents the statement is $7.50h.

She wants to earn at least $200, "at least" means more or equal (≥200).

Mathematically speaking:

  • $7.50 h ≥200

This is the inequality that represents all of the possible numbers of hours (h) the student could work to meet her goal.

For the second part we simply solve the inequation:

7.50 h  ≥200

h ≥200/7.50

h ≥ 26.67  

Rounded to the nearest whole number:

h ≥ 27  

She needs to work  27 hours to earn at least $200.

Total amount of cash the student earns per hour is $7.5, let the time taken to earn $200 be h, thus the inequality representing this will be:
7.5h≤200
thus
h≤80/3
writing in whole  numbers we shall have:
h≤27

From the sum of 3x+ 5y -2 and 2x-3y +1 subtract the sum of 4x -8y +3 and -5x + 6y +7

Answers

Answer:

First, let's simplify both sums by combining like terms:

3x + 5y - 2 + 2x - 3y + 1 = 5x + 2y - 1

4x - 8y + 3 - 5x + 6y + 7 = -x - 2y + 10

Now we can subtract the second sum from the first:

(5x + 2y - 1) - (-x - 2y + 10) = 5x + 2y - 1 + x + 2y - 10

Simplifying this expression, we get: 6x + 4y - 11